Pace bowlers in cricket with history of lumbar stress fracture have increased risk of lower limb muscle strains, particularly calf strains - John Orchard; Patrick Farhart; Alex Kountouris; et al (Dove Medical Press, 2010)
John Orchard1, Patrick Farhart2, Alex Kountouris3, Trefor James3, Marc Portus31School of Public Health, University of Sydney, Australia; 2Punjab Kings XI team, Indian Premier League, India; 3Cricket Australia, Melbourne, AustraliaObjective: To assess whether a history of lumbar stress fracture in pace bowlers in cricket is a risk factor for lower limb muscle strains.Methods: This was a prospective cohort risk factor study, conducted using injury data from contracted first class pace bowlers in Australia during seasons 1998–1999 to 2008–2009 inclusive. There were 205 pace bowlers, 33 of whom suffered a lumbar stress fracture when playing first class cricket. Risk ratios ([RR] with 95% confidence intervals[CI]) were calculated to compare the seasonal incidence of various injuries between bowlers with a prior history of lumbar stress fracture and those with no history of lumbar stress fracture.Results: Risk of calf strain was strongly associated with prior lumbar stress fracture injury history (RR = 4.1; 95% CI: 2.4–7.1). Risks of both hamstring strain (RR = 1.5; 95% CI: 1.03–2.1) and quadriceps strain (RR = 2.0; 95% CI: 1.1–3.5) were somewhat associated with history of lumbar stress fracture. Risk of groin strain was not associated with history of lumbar stress fracture (RR = 0.7; 95% CI: 0.4–1.1). Other injuries showed little association with prior lumbar stress fracture, although knee cartilage injuries were more likely in the non-stress fracture group.Conclusion: Bony hypertrophy associated with lumbar stress fracture healing may lead to subsequent lumbar nerve root impingement, making lower limb muscle strains more likely to occur. Confounders may be responsible for some of the findings. In particular, bowling speed is likely to be independently correlated with risk of lumbar stress fracture and risk of muscle strain. However, as the relationship between lumbar stress fracture history and calf strain was very strong, and that there is a strong theoretical basis for the connection, it is likely that this is a true association.Keywords: cricket, fast bowling, stress fractures, hamstring strain, calf strain